Erenumab Discontinuation After 12-Month Treatment: A Multicentric, Observational Real-Life Study. Issue 6 (December 2021) - Schiano di Cola, Francesca; Caratozzolo, Salvatore; Venturelli, Elisabetta; Balducci, Ubaldo; Sidoti, Vincenzo; Pari, Elisa; Costanzi, Chiara; di Summa, Alfonsina; Sixt, Gabriele Johanna; D'Adda, Elisabetta; Liberini, Paolo; Rao, Renata; et al.
Abstract : Objective: To assess migraine outcome after 12-month treatment with erenumab and compare patients who underwent 3-month erenumab discontinuation following the first treatment cycle with those who continued monthly administrations. Methods: This is a multicentric observational study in patients with migraine in treatment with erenumab. After a full 12-month treatment cycle (T 12 ), patients could either continue or discontinue erenumab for at least 3 months. Patients who underwent treatment discontinuation were assessed after 3 months (T 15 ) to decide whether to start retreatment. Patients were then assessed following at T 16 and T 18 . Results: Thirty consecutive patients were enrolled. Nineteen patients underwent treatment suspension at T 12 up to T 15, whereas 11 continued prophylaxis. At T 15, patients who discontinued treatment documented significantly more migraine days (17.06 ± 6.5 vs 4.8 ± 2.5; p < 0.0001) and analgesics consumption (14.8 ± 9.2 vs 4.6 ± 2.5; p = 0.002), compared with those who continued treatment. After retreatment, at T 16, patients who had previously undergone discontinuation documented a significant improvement in terms of migraine days (9.01 ± 4.4 vs 17.06 ± 6.5; p < 0.0001) and analgesics consumption (9.6 ± 7.3 vs 14.8 ± 9.2; p = 0.004). Such improvement was even greater at T 18, comparable with T 12 . Conclusion: After treatment discontinuation, a rapid migraine worsening was found, despite the high clinical response during treatment and at retreatment, which might be secondary to an untimely interruption of a potentially disease-modifying pharmacologic intervention. Although clinical improvement was documented after retreatment, given the high frequency and degree of worsening during discontinuation, it seems plausible—even ethical—to re-evaluate current timing of discontinuation. Classification of Evidence: This study provides Class III evidence that people with migraine discontinuing erenumab migraine prophylaxis after 12 months were more likely to have an increase in nonresponder status and migraine days than those who continued treatment.